Pengaruh Penggunaan Digital payment dan Literasi Keuangan Syari'ah Terhadap Perilaku Konsumtif - Ruhliandini, Putri Zafira; Mayanti, Yuni; Kamali, Ahmad Nurkamali; Maharani, Indah Maharani (Ma'soem University, 2025)
The rapid development of financial technology and the massive penetration of digital payment among students raise concerns about the increase in consumptive behavior due to the transaction ease that reduces the